Sistema olimpijskoj podgotovkisportsmenov v Norvegii - Platonov, V.; Pavlenko, I.; Tomashevskyi, V. (Science in Olympic Sport, 2018)
Objective. To carry out an analytical review and to identify the features of the system of Olympic training of athletes in Norway. Methods. Analysis and generalization of scientific and documentary data. The material for the study was information on the main components of high performance sport and Olympic training, which determine the success of Norwegian athletes at the Olympic Games since 1992. Results. The sporting achievements of the Norwegian national team at the Winter Olympics, which is second only to German athletes, are far superior to those of many countries with a high level of development of winter sports. A number of factors were found to contribute to this development, including the establishment of a centralized training system for the strongest athletes based on the generalized experience of the former socialist countries and the creation of the Olympiatop-pen organization; differentiated financing of national sports federations and organizations from various alternative sources; development, generalization, analysis, and introduction of new knowledge and best practices; creation of a powerful modern material and technical foundation with a network of sports training centers; balancing of athletes training and education, their personal and social life; comprehensive physical education and formation of a healthy lifestyle of children with the exception of unnecessary early specialization and forced preparation; multi-stage organization of the multi-year training of high-class athletes. Conclusions. The achievements of the Norwegian athletes at the Olympic Games are the result of a well-thought-out and well-implemented Olympic training system, in which rich national traditions and achievements are successfully complemented by advanced world experience and knowledge. Norway has convincingly demonstrated that a country with a very limited human resource, when a rational organization of business and an advanced, scientifically sound training method are used, is capable of successfully competing with big sports countries, which have commensurately greater resources.